The prevalence and tracking of overweight and obesity in a cohort of youths. Natural development of body mass index from childhood to adolescence. A sub study of the Fit Futures cohort. - Evensen, Elin Kristin (Universitetet i Tromsø, 2013)
Objectives: The purpose of this master project was to: obtain height and weight data at three measuring points (2-4 years of age, preschool age and adolescence) in a Norwegian cohort of youths, to estimate prevalence rates of weight classes, describe the natural development of body mass index (BMI) from childhood to adolescence, and to investigate to what extent tracking of overweight and obesity was present. Methods: In a retrospective cohort design the Fit Futures cohort was supplemented with data from childhood health records. 532 participants were included in cross sectional and longitudinal data analyses. Tracking was analysed using correlation, Cohen’s weighted Kappa and logistic regression. BMI development was analysed using non-parametric tests. Descriptive data and prevalence rates for weight class, waist circumference (WC) and waist height ratio are presented (WHtR). Classification in weight classes: thin, normal weight, overweight and obese, was done according to International Obesity Taskforce age and sex specific cut-off values for children 2-18 years. Results: 8,6 - 9,7 % of boys and 14,6 – 18,1 % of girls in childhood and 20,5 % boys and 19,7 % girls at adolescence were classified as overweight/obese. BMI decreased from 2-4 years to preschool age and increased to adolescence, following the natural change in BMI in childhood. More than 80 % stayed thin/normal weight between childhood and adolescence. Tracking of overweight/obesity was present. Being overweight/obese at preschool age increased the odds of being overweight/obese at adolescence, compared to normal/thin OR: 11,1 (CI: 6,4-19,2). Tracking of overweight/obesity between 2-4 years of age and adolescence was weaker and not significant for boys. Results of correlation and weighted Kappa analyses were in accordance with results from logistic regression. From 13,2% to 22,6 % changed their weight class between measuring points in childhood and adolescence. 19,0 % of boys and 20,9 % of girls had a WHtR ≥ 0,5, the recommended cut-off point for defining central obesity. Conclusion: The prevalence of overweight/obesity increased with age. Prevalence rates were in accordance with earlier findings from North Norway, and are generally higher than rates reported from other regions of Norway, with some exceptions. Overall, development in BMI followed a natural growth curve and the majority stayed thin/normal weight. We found moderate to strong indication of tracking of overweight/obesity, especially from preschool age to adolescence. Tracking was strongest among girls. Many children also changed their weight class during childhood. WC and WHtR identified a higher proportion with central overweight/obesity than comparable Norwegian studies, especially among girls.